2020
DOI: 10.1155/2020/7480204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aromatherapy with Lavender and Peppermint Essential Oils on the Sleep Quality of Cancer Patients: A Randomized Controlled Trial

Abstract: One of the problems of cancer patients is sleep disorder. Given the absence of studies on comparing the effect of inhalation aromatherapy with lavender and peppermint on the sleep quality of the cancer patients, this study was performed to compare the effect of inhalation aromatherapy with lavender and peppermint essential oils on the sleep quality of cancer patients. For this purpose, 120 patients were randomly allocated to three groups of lavender, peppermint, and control. The intervention groups received th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 29 publications
1
44
0
3
Order By: Relevance
“…Ahmad et al [24] conducted a single-blind, randomized, placebo-controlled trial in male pharmacy students to evaluate the effect of aromatherapy with lavender oil on academic stress during the exams and concluded that academic stress was not improved by the aromatherapy with lavender oil. Hamzeh et al [25] conducted a randomized controlled trial to investigate the effect of aromatherapy with lavender essential oil and peppermint essential oil on the sleep quality of cancer patients. Exposure to essential oil (lavender essential oil or peppermint essential oil) reduced the Pittsburgh Sleep Quality Inventory (PSQI) in the cancer patients of the intervention group compared to that of the control group indicating that aromatherapy could improve the quality of sleep of cancer patients [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahmad et al [24] conducted a single-blind, randomized, placebo-controlled trial in male pharmacy students to evaluate the effect of aromatherapy with lavender oil on academic stress during the exams and concluded that academic stress was not improved by the aromatherapy with lavender oil. Hamzeh et al [25] conducted a randomized controlled trial to investigate the effect of aromatherapy with lavender essential oil and peppermint essential oil on the sleep quality of cancer patients. Exposure to essential oil (lavender essential oil or peppermint essential oil) reduced the Pittsburgh Sleep Quality Inventory (PSQI) in the cancer patients of the intervention group compared to that of the control group indicating that aromatherapy could improve the quality of sleep of cancer patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hamzeh et al [25] conducted a randomized controlled trial to investigate the effect of aromatherapy with lavender essential oil and peppermint essential oil on the sleep quality of cancer patients. Exposure to essential oil (lavender essential oil or peppermint essential oil) reduced the Pittsburgh Sleep Quality Inventory (PSQI) in the cancer patients of the intervention group compared to that of the control group indicating that aromatherapy could improve the quality of sleep of cancer patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…Compare (16) to (6) to get the ideal PID controller as below, Hence, the tuning parameter of an ideal PID controller based IMC strategy can be obtain by (18) The fractional-order filter parameter from (13) that given in (19) Table 1 shows the calculated value of α and time constant τ c calculated using (19) for a desired phase margin and crossover frequency while the Bode plot is shown in Figure 5. Crossover frequency ω c is constant value of 0.008 which one of the controller design criteria in [25].…”
Section: Imc Pid With Fractional-order Filtermentioning
confidence: 99%
“…Essential oils are primarily used in the flavour, fragrance, cosmetics and pharmaceutical industries [1][2][3][4]. The essential oils contain a complex mixture of volatile chemical compounds and they are sensitive towards temperature which may affect the quality of the oils [5][6][7]. Steam distillation is one of the effective and affordable methods used to maintain a strict temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Antiemetic activity of volatile oil from Mentha spicata and Mentha piperita has been also reported in chemotherapy-treated patients [ 253 ]. A recent randomized controlled trial with 120 patients evidenced the efficacy of aromatherapy with lavender and peppermint EOs in improving the sleep quality of cancer patients [ 254 ]. Linalool, linalyl acetate and menthol present in lavender or peppermint EOs [ 255 , 256 ] can be responsible of EOs effect on sleep due to their sedative effects.…”
Section: Clinical Use Of Eos For Cancer Patientsmentioning
confidence: 99%